2019
DOI: 10.1051/limn/2018030
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting aquatic beetle communities of Northern Western Ghats of India (Arthropoda: Insecta: Coleoptera)

Abstract: We studied faunistic and ecological factors influencing distributions of aquatic beetles in the Northern Western Ghats (NWG) of India. In the period 2013–2017, we collected 213 samples from 105 localities within the area and obtained 66 species, the majority of which belong to Dytiscidae. Relative occurrence based on incidence data revealed that dytiscid water beetle Laccophilus inefficiens as the most widespread species. Non-parametric richness estimators Chao2, Jackknife1 and Bootstrap showed that 70–80% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…in Mindanao Island. This trend in species-specific distribution to a limited altitudinal range has been documented in beetles (Maveety et al 2011;Koutroumpa et al 2013;Sheth et al 2019).…”
Section: Discussionmentioning
confidence: 54%
“…in Mindanao Island. This trend in species-specific distribution to a limited altitudinal range has been documented in beetles (Maveety et al 2011;Koutroumpa et al 2013;Sheth et al 2019).…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, Neohydrocoptus bivittis is recorded for the first time from the Konkan region, westward to the northern Western Ghats of Maharashtra. This suggests that the water beetle fauna of Maharashtra has perhaps been underestimated and intensive surveys may reveal a few more known species or even new species (Sheth et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For the present work, we focused on freshwater habitats in the northern Western Ghats (hereafter referred to as NWG) of Maharashtra State (locality and habitat details are according to Sheth et al 2019). NWG are one of eight parts of the Deccan plateau formed due to volcanic eruptions (Image 1A).…”
Section: Study Areamentioning
confidence: 99%
“…They harbor various endemic organisms uniquely adapted to the highly variable environment in the open ecosystem (Watve, 2013; Gaitonde et al, 2016). There is existing information on arthropod and aquatic plant communities (Sheth et al, 2019; Kulkarni et al, 2022; Kulkarni et al, 2023), but vertebrate ecology, especially of tadpoles, is lacking. Jithin et al .…”
Section: Introductionmentioning
confidence: 99%
“…They harbor various endemic organisms uniquely adapted to the highly variable environment in the open ecosystem (Watve, 2013;Gaitonde et al, 2016). There is existing information on arthropod and aquatic plant communities (Sheth et al, 2019;Kulkarni et al, 2022;Kulkarni et al, 2023), but vertebrate ecology, especially of tadpoles, is lacking. Jithin et al (2023) showed that large FRPs are important for adults of three species of frogs: Euphlyctis jaladhara, Microhyla nilphamariensis, and Polypedates maculatus; and recommended restoration or creation of rock pools for amphibian conservation in light of reduced FRP availability because of rapid conversion of outcrops to orchards that reduces the availability of FRPs.…”
Section: Introductionmentioning
confidence: 99%